Island medicine: using data linkage to establish the kidney health of the population of Tasmania, Australia.: Kidney disease in Tasmania - Jose, Matthew; Raj, Rajesh; Jose, Kim; Kitsos, Alex; Saunder, Tim; McKercher, Charlotte; Radford, Jan (International Journal of Population Data Science, 2021)
Objective To report (using linked laboratory data) the incidence, prevalence and geographic variation of chronic kidney disease (CKD) across the whole island population of Tasmania, Australia. Methods A retrospective cohort study (the Tasmanian Chronic Kidney Disease study (CKD.TASlink)) using linked data from five health and two pathology datasets from the island state of Tasmania, Australia between 1/1/2004 and 31/12/2017. We used data on 460,737 Tasmanian adults (aged 18 years and older, representing 86.8% of the state's population) who had a serum creatinine measured during the study period. We defined CKD as per Kidney Disease Outcomes Quality Initiative, requiring two measures of estimated glomerular filtration rate (eGFR) <60 mL/min/1.73m2, at least three months apart. Kidney replacement therapy (KRT) included dialysis or kidney transplantation. Results We identified 56,438 Tasmanians with CKD during the study period, equating to an age-standardised annual incidence of 1.0% and a prevalence of 6.5%. These figures were higher in women, older Tasmanians and people living in the North-West region of Tasmania. Testing for urinary albumin:creatinine ratio is increasing, with 28.5% of women and 30.8% of men with stage 3 CKD having both an eGFR and uACR in 2017. Use of KRT was consistently seen in >65% of Tasmanians with eGFR <15mL/min/1.73m2. Conclusion There is geographic and gender variation in the incidence and prevalence of CKD, but it is reassuring to see that the majority of people with end-stage kidney failure are actually receiving treatment with dialysis or transplantation.